2010
DOI: 10.1097/pas.0b013e3181fc714d
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cardiac Polyps

Abstract: As endoscopists have become more skilled in sampling the gastroesophageal junction, pathologists are being increasingly challenged to characterize previously unknown or neglected findings. One such example is the cardiac polyp. Originally described in the radiology literature as the sentinel fold, the first histologic descriptions of polyps at the gastroesophageal junction did not appear until less than a decade ago. Current clinicopathologic information is limited and somewhat conflicting. This study was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Cardiac polyps are usually benign, are usually less than 1 cm, and are not associated with esophagitis, Barrett’s esophagus, gastroesophageal reflux, or gastritis. 3 Cases of large polyps causing intermittent pyloric obstruction, with the resultant symptoms, have been reported. 1 However, similar cases of gastric polyps leading to esophageal obstruction have not been identified in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac polyps are usually benign, are usually less than 1 cm, and are not associated with esophagitis, Barrett’s esophagus, gastroesophageal reflux, or gastritis. 3 Cases of large polyps causing intermittent pyloric obstruction, with the resultant symptoms, have been reported. 1 However, similar cases of gastric polyps leading to esophageal obstruction have not been identified in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which HPs develop through presumed proliferation of the foveolar surface mucosa is not known, but since they are localised, there must be a local change in the growth regulation or a mutation in the cell of origin affecting the proliferation rate. HPs also develop in the cardia [ 87 ] of patients with gastroesophageal reflux disease (GERD). Hypertrophic gastropathy in Ménétriers disease, a condition of uncertain etiology, but with increased risk of gastric cancer development, may also contain elements that mimic HPs [ 88 ].…”
Section: Gastric Polypsmentioning
confidence: 99%
“…Among all patients with gastric polyps, 11% are found to have cardia polyps 6 . Cardia polyps are defined as pedunculated or sessile lesions that originate from the mucosal epithelium of the cardia that protrude into the cavity 7 . It has been reported that malignant transformation can be seen in 0.42% of hyperplastic polyps and in 23.1% of adenomatous polyps in the stomach 8 .…”
Section: Introductionmentioning
confidence: 99%